The Impact of Marketing Communications on Buying Silver Online: Study on Young Generation’s Perception in Malaysia - Goi, Chai; Fu, H.; Ting, W.; Goh, W.; Chin, S. (International Association of Computer Science and Information Technology Press (IACSIT Press), 2013)
The main objective of this research is to study the impact of marketing communications on buying silver online, especially perception of young generation in Malaysia. This study found that all marketing communications tools, advertising, online marketing, personal selling, public relations and sales promotion are important and significant impact on buying silver online.